1955
DOI: 10.1039/tf9555101529
|View full text |Cite
|
Sign up to set email alerts
|

The semiconductivity of organic substances. Part 2

Abstract: t The " energy gap " is the term AE in the equation for the conductivity K = KO exp (-Ae/2kT) and is usually given in electron-volts (see ref.(17)). The earlier paper 4 gave A 4 2 values in kcal/mole, listed as E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

1960
1960
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(49 citation statements)
references
References 0 publications
1
47
0
1
Order By: Relevance
“…18,19 The thin film (diameter, 1 cm; thickness, 1 mm) was tightly adjusted between the plates of two copper electrodes of an electric cell. The cell was put in an electric furnace that was connected to a thermocouple for measuring the temperature.…”
Section: Measurement Of Specific Electric Conductivitymentioning
confidence: 99%
“…18,19 The thin film (diameter, 1 cm; thickness, 1 mm) was tightly adjusted between the plates of two copper electrodes of an electric cell. The cell was put in an electric furnace that was connected to a thermocouple for measuring the temperature.…”
Section: Measurement Of Specific Electric Conductivitymentioning
confidence: 99%
“…This idea initiated research on the band structure and semiconducivity of organic molecules [111][112][113][114][115], which resulted in multiple attempts to apply semiconductor theory to describe the adsorption-induced conductivity changes of biopolymers [116][117][118][119][120][121]. Recently, near room temperature hopping conduction of ionic charge carriers and holes was suggested in onedimensional TiO x [122] and Mo 6 S y I z [123,124] nanostructures and certain biopolymers [125,126], which was gradually replaced by fluctuation induced tunneling with decreasing temperature [127].…”
Section: Surface Conducting Mechanismsmentioning
confidence: 99%
“…they behave as semiconductors. Eley and Par®tt [1,2] have shown that some chelated compounds like phthalocyanin and copper-phthalocyanin have semiconducting properties. Organic compounds with paramagnetic properties are found among simple organic molecules [3,4], proteins [5] dyes [6] and chelated compounds as well as polymers [7].…”
Section: Introductionmentioning
confidence: 99%